Life-Cycle Assessment of the Production of Rare-Earth Elements for Energy Applications: A Review - Navarro, Julio; Zhao, Fu (Frontiers in Energy Research, 2014)
Rare-earth elements (REEs) are a group of 17 elements with similar chemical properties, including 15 in the lanthanide group, yttrium, and scandium. Due to their unique physical and chemical properties, REEs gain increasing importance in many new energy technologies and systems that contribute to reduce greenhouse gas emissions and fossil fuel depletion (e.g., wind turbine, electric vehicles, high efficiency lighting, batteries, and hydrogen storage). However, it is well known that production of REEs is far from environmentally sustainable as it requires significant material and energy consumption while generating large amounts of air/water emissions and solid waste. Although life-cycle assessment (LCA) has been accepted as the most comprehensive approach to quantify the environmental sustainability of a product or process, to date, there have been only very limited LCA studies on the production of REEs. With the continual growth of renewable energy and energy efficient technologies, global production of REEs will increase. Therefore, reducing environmental footprints of REE production becomes critical and identifying environmental hotspots based on a holistic and comprehensive assessment on environmental impacts serves as an important starting point. After providing an overview of LCA methodology and a high-level description of the major REE production routes used from 1990s to today, this paper reviews the published LCA studies on the production of REEs. To date, almost all the LCA studies are based on process information collected from the operation of Mountain Pass facility in U.S. in 1990s and the operation of facilities in Bayan Obo, China. Knowledge gaps are identified and future research efforts are suggested to advance understanding on environmental impacts of REE production from the life-cycle perspective.